USE OF BIOGENIC PEPTIDES IN COMPLEX TREATMENT OF INFLAMMATORY DISEASES OF PARODONT IN PATIENTS WITH DIABETES MELLITUS II TYPE - Usmonov Bakhtiyorjon Arobidin ogli (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The significance of periodontal pathology in patients with type 2 diabetes mellitus is determined not only by the high prevalence, but also by the multifactorial genesis of the disease, which negatively affects the body as a whole, ultimately leading to a low efficiency of the treatment, and, most importantly, the duration of preservation achieved therapeutic effect [1,4]. In this regard, a promising direction in the complex treatment of periodontitis in patients with type 2 diabetes is the use of peptide bioregulators capable of regulating local immune, microcirculatory and oxidative disorders in the periodontal tissues, but not causing dysbiotic changes in the oral cavity [2, 3].